THAI VENDORS’ ENGLISH COMMUNICATION SKILL NEEDS: Received: 06th September 2021; Revised: 21st March 2022, 26th March 2022, 30th March 2022; Accepted: 06th April 2022 - Toomnan, Parichart; Putsyainunt, Bodee (PUPIL: International Journal of Teaching, Education and Learning, 2022)
The aim of the study was to examine the needs and problems of Thai vendors in employing English in their workplace and their needs regarding English training, and subsequently to create an English training course to enhance their professional skills. The subject of the present study were 160 vendors selling food and drinks, clothes, accessories, souvenirs, and other things at the Indochina Market, Thailand. The data were collected by using a questionnaire. Descriptive statistics were used to analyze the data, involving frequency, percentage, mean, and standard deviation. The result revealed that respondents tended to have English communication problems with foreign customers. They found that low English language proficiency is a problem when communicated with foreign customers. Most of them were interested in attending English training, particularly learning English online. Speaking and listening skills were considered the most important skills for these Thai vendors. For an English training course, they wanted to emphasize speaking, listening, writing, and reading, respectively. They desired to improve their English in everyday life and work.